METODE PENELITIAN HUKUM NORMATIF DAN EMPIRIS: KARAKTERISTIK KHAS DARI METODE MENELITI HUKUM - sonata, depri liber (FIAT JUSTISIA, 2014)
The aim in this article is to determine the method of normative and empirical legal research with the typical characteristics of the methods of researching Law. The approach used qualitative methods through the study of literature. Based on the research findings and discussion, it can be concluded, first, science law (jurisprudence) and all sub-study with him in a large family study of the law, no matter how controversial as as a discipline independent and peculiar (sui generis), part from the humanities and social sciences, as well as natural science (exact) and social sciences which has had an undeniable place in the branches of science. Science of law must be recognized as having the research methods typical and unique, in terms of interest / usefulness to do a research in the field of law, both theoretical and practical, or of how to look at the science of law as a discipline prescriptive and applied, as well as from the point of view of human behavior relating to the existence of the law. Secondly, the penstudi law should realize the importance of legal research which is the authority, even advised not to leave, ie normative legal research / doctrinal, both from the point of view of the approach commom law system (statutes approach, case approach, historical approach, comparative approach and conceptual approach) as well as from the standpoint of research form the principles of law, the synchronization of legislation and others. which has been used as a handle by penstudi law in Indonesia and tend intended for academic interest. Third, the differences in conceptions, notions in the study of legal research in various law schools and high schools of law, especially for academic interest (thesis and dissertation), the main question is whether or not a uniformity is realized, or let it all by referring to the belief respective legal research on how it thinks best.Â Keywords: Research Methods law, Legal Normative and Empirical